Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
30th AIAA Applied Aerodynamics Conference 2012
DOI: 10.2514/6.2012-3326
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Flow Investigation of Morphing Leading Edges for the Enhancement of Maneuverability of Unmanned Combat Air Vehicles

Abstract: Observing the progress in the technology of unmanned combat aerial vehicles (UCAVs) than it can be foreseen that in future the role of manned combat aircraft will be taken over more and more by unmanned systems. The abandonment of pilots allows for more freedom in the aerodynamic and structural design of vehicles in regard to weight or acceleration. However, new stealth constraints will have a severe impact on the freedom of scope. The design of UCAV configurations is driven by the special requirements of upco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The suffix "E" (for "intake", in German "Einlauf") was added to indicate that the model contains a modular center body section that can be exchanged with a flow-through inlet section. The effect of the inlet as well as various leading edge shapes have been studied in previous high-speed tests of the DLR F17E [11]- [13].…”
Section: Dlr-f17e High Speed Modelmentioning
confidence: 99%
“…The suffix "E" (for "intake", in German "Einlauf") was added to indicate that the model contains a modular center body section that can be exchanged with a flow-through inlet section. The effect of the inlet as well as various leading edge shapes have been studied in previous high-speed tests of the DLR F17E [11]- [13].…”
Section: Dlr-f17e High Speed Modelmentioning
confidence: 99%
“…Morphing aircraft is a promising technology that can help in mitigating the adverse effects of flight and meet the FlightPath 2050 goals. In addition, morphing wings can increase maximum lift, reduce drag [2,3] and vibrations, improve flight performance within a certain airspeed range [4], and enhance aeroelastic performance [5,6] and aircraft maneuverability [7,8]. By definition, a morphing aircraft continuously adjusts its geometry to enhance flight performance, control authority, and multi-mission capability.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of morphing has attracted widespread attention from present aircraft designers [1]. It is found that morphing wings can improve the overall flight efficiency by adapting to different flight conditions by adjusting their shapes [2], and can improve their performance within a certain airspeed range, reduce vibration [3], increase maximum lift, reduce drag [4,5], or enhance aircraft maneuverability [4,6,7] and aeroelastic performance [8,9]. In addition, due to the reduction of discontinuous rudder surfaces, morphing wings can further improve the stealth performance [2].…”
Section: Introductionmentioning
confidence: 99%